Autologous Bone Marrow Stem Cells in the Treatment of Chronic Liver Disease - Madhava Pai; Duncan Spalding; Feng Xi; Nagy Habib (International Journal of Hepatology)
Chronic liver disease (CLD) is increasing worldwide yet there has been no major advance in effective therapies for almost five decades. There is mounting evidence that adult haematopoietic stem cells (HSC) are capable of differentiating into many types of tissue, including skeletal and cardiac muscle, neuronal cells, pneumocytes and hepatocytes. These recent advances in regenerative medicine have brought hope for patients with liver cirrhosis awaiting transplantation. New findings in adult stem cell biology are transforming our understanding of tissue repair raising hopes of successful regenerative hepatology. Although all clinical trials to date have shown some improvement in liver function and CD34+ cells have been used safely for BM transplantation for over 20 years, only randomised controlled clinical trials will be able to fully assess the potential clinical benefit of adult stem cell therapy for patients with CLD. This article focuses on the potential of bone marrow stem cells (BMSCs) in the management of CLD and the unresolved issues regarding their role. We also outline the different mechanisms by which stem cells may impact on liver disease.